CFD investigation on hydrogen enrichment effect to dual-fuel direct injection diesel engine - K Frhan, Nhad (2021)
The engine as an integral and most important part of the vehicle which the mechanical power used in moving the automobile. Compression Ignition (CI) engines are use in driving heavy duty machines and power generation plants due to the 40% higher efficiency and torque compared to the Spark Ignition (SI) engines. Bulk of previous studies on the use of alternative fuels; hydrogen-natural gas blends (HCNG) used port injection and experimentally were conducted. The use of Computational Fluid Dynamics (CFD) simulations in analyzing the effect of adding (0 - 90) % hydrogen to blend fuel and varying the equivalence ratio (0.6-1.4) on the combustion and exhaust emission characteristics are not intensively studied. Especially when using direct injection (DI) technique. The aim of this study was to develop a reliable CFD model capable of predicting the key parameters in the combustion process of a DI-diesel engine. The study investigated the relationship between hydrogen and variations in equivalence ratio on the air-fuel dynamic flow and emissions characteristics. The simulation using HCNG was conducted at various hydrogen doses (0 – 90) % along equivalence ratios of 0.6 -1.4 at a step of 0.2. The constant engine speed was 1500 rpm at low load condition. The developed CFD model was validated for reliability using a comparative analysis with other experimental study. The result of validation showed that the CFD model was in close agreement with the experimental work used in confirmation. The addition of 0% - 90% hydrogen increased the in-cylinder temperature from 1017 K at 0% to 1200 K at 90 %, when the equivalence ratio was 0.6. At 90 % added hydrogen, the maximum in-cylinder temperature of 1424 K was obtained. A reduction in the in-cylinder pressure from 3.200 bar at 0% hydrogen to 2.872 bar was obtained at 90 %. Increase in equivalence ratio increased pressure to 3.228 bar at 1.4 equivalence ratio and 0 % hydrogen. Heat release rate (HRR) increased when both mole fraction of hydrogen and equivalence ratio increased, with 37.98 KJ as the maximum heat release rate observed at 90 % hydrogen addition and 1.4 equivalence ratio.